Population genomics of transposable element activation in the highly repressive genome of an agricultural pathogen. Issue 8 (23rd August 2021) - Pereira, Danilo; Oggenfuss, Ursula; McDonald, Bruce A.; Croll, Daniel
Abstract : The activity of transposable elements (TEs) can be an important driver of genetic diversity with TE-mediated mutations having a wide range of fitness consequences. To avoid deleterious effects of TE activity, some fungi have evolved highly sophisticated genomic defences to reduce TE proliferation across the genome. Repeat-induced point mutation (RIP) is a fungal-specific TE defence mechanism efficiently targeting duplicated sequences. The rapid accumulation of RIPs is expected to deactivate TEs over the course of a few generations. The evolutionary dynamics of TEs at the population level in a species with highly repressive genome defences is poorly understood. Here, we analyse 366 whole-genome sequences of Parastagonospora nodorum, a fungal pathogen of wheat with efficient RIP. A global population genomics analysis revealed high levels of genetic diversity and signs of frequent sexual recombination. Contrary to expectations for a species with RIP, we identified recent TE activity in multiple populations. The TE composition and copy numbers showed little divergence among global populations regardless of the demographic history. Miniature inverted-repeat transposable elements (MITEs) and terminal repeat retrotransposons in miniature (TRIMs) were largely underlying recent intra-species TE expansions. We inferred RIP footprints in individual TE families and found that recently active, high-copy TEs have possibly evaded genomic defences. We find no evidence that recent positive selection acted on TE-mediated mutations rather that purifying selection maintained new TE insertions at low insertion frequencies in populations. Our findings highlight the complex evolutionary equilibria established by the joint action of TE activity, selection and genomic repression.